Burden of GB Carcinoma among people from Terai, and Hill/ Himalayan regions of Nepal - Sapkota, Ganga; Mallik, Dipendra Kumar; Sapkota, Ashok; Dhakal, Sunil; Mishra, Roshan (Nepalese Journal of Cancer, 2018)
Background: GB carcinoma is rare cancer worldwide, but is sixth most common cancer among females in Nepal. Burden of GB carcinoma has geographical and ethnic variation. This study mainly focuses on geographical distribution of GB carcinoma, among Nepalese patients visiting BPKMCH. Methods and materials: We conducted a retrospective study approved by Department of GI Surgery, BP Koirala Memorial Cancer Hospital, Bharatpur, Nepal. Datas were collected from Jan 1,2107 to 31st Dec 2017 from medical record sections. Analysis was completed using SPSS. Results: A total number of 340 patients were recorded, comprising 220 patients with malignancy and 115 patients with benign lesions, and remaining 5 patients files could not be traced. Among malignant patients 158 were female, and 62 were male, with male to female ratio (M: F) of 1:2.5. In malignant group, patients from terai were 70%, hilly and Himalayan region were 30%. Conclusion: The data provides clue on burden of GB carcinoma being relatively high in female, and terai region of Nepal.